Narration the Jews in the Qur'an - Zulkarnaini, Zulkarnaini; Marhaban, Nawawi; Nurdin, Nurdin (Ridwan Institute, 2025)
The history of the Jewish nation is a complex topic, encompassing various historical, theological, and moral dimensions, one of which is outlined in the Qur'an. The narration of the Jews in the Qur'an, scattered throughout various surahs and verses, often highlights their behavior—both exemplary and avoidable—as a lesson for humanity. This research aims to analyze in depth the Jewish nation as mentioned in the Qur'an. The research method used is qualitative, with data collection techniques through documentation. After the data are collected, the analysis is carried out by reducing the data, presenting the data, and drawing conclusions. The results of the study show that the narration of the Jewish people in the Qur'an includes praise of them as descendants glorified by God and illustrates the various extraordinary gifts given to the Jewish people. These verses were revealed to provide lessons and warnings to the Prophet Muhammad and Muslims to face challenges patiently and believe that the truth will ultimately prevail. In addition, the Qur'an also explains that the Jews made mistakes that led to God's wrath, offering a warning about the consequences of iniquity.